2002
DOI: 10.1002/1521-4095(20021203)14:23<1735::aid-adma1735>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Mild Thermal Treatment on the Performance of Poly(3-alkylthiophene)/Fullerene Solar Cells

Abstract: A three‐ to four‐fold increase in power conversion efficiency is reported for poly(3‐alkylthiophene)/fullerene solar cells by simply heating the device to 55 °C for 30 min. This behavior may be due to enhanced diode properties, plus a higher degree of order within the material. The Figure shows the soluble fulleropyrrolidine used as electron acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 8 publications
4
113
2
Order By: Relevance
“…Similar results have been reported by other authors. [10,30] Furthermore, the mobility measurements presented in Figure 3, correlated with the morphology investigations [15,[27][28][29] indicate that there is a change in the physical conformation of the P3HT chains. As a result, the packing …”
Section: Optical Absorption Spectrasupporting
confidence: 57%
“…Similar results have been reported by other authors. [10,30] Furthermore, the mobility measurements presented in Figure 3, correlated with the morphology investigations [15,[27][28][29] indicate that there is a change in the physical conformation of the P3HT chains. As a result, the packing …”
Section: Optical Absorption Spectrasupporting
confidence: 57%
“…[6,21,22] It has been widely reported that the P3HT absorption red-shifts and a series of vibronic peaks become visible at k ∼ 600 nm, 550 nm, and 510 nm. [6,11] This red-shift has been assigned to increased planarization and stabilization of the P3HT chains that accompanies self-stacking of the polymer.…”
Section: By Adam J Moulé and Klaus Meerholz*mentioning
confidence: 99%
“…Results from these studies point out that the optimum blend ratio is between 1:0.9 and 1:1, but fail short of specifying the exact optimal ratio (Woehrle and Meissner, 1991). Some other studies however have made mention of 1:1 as the optimal ratio while others have mentioned 1:0.80 or 1:0.43 (Camaioni et al, 2002;Dennler et al, 2009;Chen et al, 2009). This study specifically focuses on the blend ratio range 1: 0.80 -1:1.…”
Section: Introductionmentioning
confidence: 97%